Analisis Implementasi Keselamatan dan Kesehatan Kerja Instalasi Radiologi Rumah Sakit X Kota Semarang - Akbar Kurniawan; Hanifa Maher Deny; Nico L Kana (Jurnal Manajemen Kesehatan Indonesia, 2017)
Occupational health and safety is one of the efforts to improve hospital services, especially in terms of health and safety for human resources of hospital, patient, visitors, and the surrounding comunity. One the hazards sources associated with K3RS in the radiation hazard that is part of the physical hazard. The radiology installation of RS X uses ionizing radiation in its services process. The purpose in this researchis to analyze the implementation of safety and health of radiology installation. Design of observational research  with qualitative approach. Population research all human resources radiology installation unit (two people). K3RS (one Person), informant triangulation medical services manager (one person). Data were collected by in depth interview and observation techniques. The results of the identification indicate the limitations of human resources training, facilities and infrastructure, budget realization and coordination. Implementation based on government regulations has been implemented, both from the number and standard of human resources education, as well as fascilities and infrastructure such as lead protection, calibration and completeness of personal protective equipment.  Some things that have been set at the beginning of plannning can not be realized, such as budgets and coordination commitments. It is advisable to increase human resources training, prioritize budgets that have been included in the initial plan, complement of incomplete facilities and infrastucture, increase the realization of the established coordination commitments